(untitled) (Psychology Travelogs, 2024)
The main resource of the staff is the core formation of the personality – its subjective resource. The concept of subjectivity is associated with such personality characteristics as individuality; independent creative thinking; character; activity; will; sense of personal social and moral responsibility; moral, psychological, emotional and volitional stability; psychological and professional readiness; psychological, moral, professional reliability; spirituality; and creative potential. One of the peculiarities in the development of both the category of subject and the concept of subjectivity is the tendency of development from the characteristics of human qualities to procedural characteristics (self-determination, self-awareness, self-regulation, etc.). The subjective resource of a personality is an important concept in psychological theory that reflects the internal potential of an individual for self-development, adaptation and achievement of life goals. This concept is based on the idea of a person as an active subject capable of actively influencing his or her own life, shaping his or her own destiny and developing psychologically. One of the most important foundations of the mechanisms of influence on real objects in order to achieve the necessary positive change is knowledge of the laws of functioning and development of mental phenomena, as well as the factors that influence them. The need to address the subjectivity of the individual is convinced by the ideas of philosophical anthropology regarding the systemic integrity of the human being, within which he or she emerged as a unity of physical, mental and spiritual principles. The subjective resource can be viewed both as a certain ideal characterised by a certain relative constancy and as a special spiritual and social substance of human existence existing in the conditions of a specific time and real space in the person of its bearers - subjects of military activity.